Kıbrıs Türk Eğitim Tarihinde Shakespeare Okulu ve Nejmi Sagıp Bodamyalızade / Shakespeare School and Nejmi Sagip Bodamyalizade in Cyprus Turkish Education History - Özkul, Ali Efdal; Özsezer, Mete (Journal of History Culture and Art Research, 2017)
Abstract Nejmi Sagıp Bodamyalızade, who was originally from Paphos in the south-west of Cyprus, completed his education at Oxford University. Then he returned to the island and established the Shakespeare School, which is one of the first private schools of the island. He has undertaken both teaching and school management roles here. Many Turkish Cypriots have been educated in this private school which offers English education. Nejmi Sagıp, which has a high level of general culture, has been nicknamed Feylosof (philosopher) by the community. During World War II, Nejmi Sagıp declared himself as a deputy of Cypriot Muslims by the signing of thousands of people in Nicosia. By using this title, Mr. Nejmi sent letters to the presidents and deputies of several countries, mainly the United Kingdom, defending the rights of Turkish Cypriots against the Enosis requests of Greek Cypriots. Mr. Nejmi has literary works besides education and political activities. One of his literary was the Quran which he translates to English. He also translated some of the classics of Turkish literature into English. Many people, especially the Irish writer George Bernard Shaw, Nobel Peace Prize-winning, have already begun to appreciate him for his translations. As a result, Mr. Nejmi has an important value for the Turkish Cypriot Political, Cultural and Educational history. Öz Aslen Kıbrıs’ın güney batısında bulunan Baf Kazasından olan Nejmi Sagıp Bodamyalızade, Oxford Üniversitesi’ndeki eğitimini tamamladıktan sonra adaya dönerek adanın ilk özel okullarından olan Shakespeare Okulu’nu kurmuştur. Burada hem öğretmenlik hem de okul müdürlüğü görevlerini üstlenmiştir. İngilizce eğitim veren bu özel okulda birçok Kıbrıslı Türk eğitim almıştır. Genel kültür düzeyi yüksek olan Nejmi Sagıp’a halk tarafından Feylosof (Filozof) lakabı takılmıştır. Nejmi Sagıp, II. Dünya Savaşı sırasında Lefkoşa’da binlerce kişiden imza toplayarak kendisini Kıbrıslı Müslümanların vekili ilan etmiştir. Nejmi Bey bu unvanı kullanarak başta İngiltere olmak üzere birçok ülkenin başkan ve elçilerine Kıbrıslı Rumların Enosis taleplerine karşı Kıbrıs Türklerinin haklarını savunan mektuplar göndermiştir. Nejmi Bey’in eğitim ve siyasi faaliyetlerinin yanında edebi çalışmaları da bulunmaktadır. Kaleme aldığı edebi eserlerinden birisi de İngilizceye çevirdiği manzum Kur’an-ı Kerim’dir. Ayrıca Türk Edebiyatının klasiklerinin bazılarını da İngilizceye tercüme etmiştir. Yaptığı bu çeviriler sayesinde başta Nobel Barış ödülü sahibi İrlandalı yazar George Bernard Shaw olmak üzere birçok kişinin takdirini toplamayı başarmıştır. Sonuç olarak Nejmi Bey Kıbrıs Türk Siyasi, Kültürel ve Eğitim tarihinin bir dönemine damgasını vurmuştur denilebilir.